Unilateral laterothoracic exanthem: of viral etiology? - Cambon, L.; Bonafé, J.L.; Icart, J.; Garcia, V.; De Riols, C. (European Journal of Pediatric Dermatology, 2018)
We report a case of unilateral laterothoracic exanthem in a little girl of 35 months in a context of primary infection by the Epstein-Barr-virus. The viral origin of this disease was only suspected up to now. We are intrigued by the polymorphism of the clinical signs associated with this viral agent.